From 'precarious informal employment' to 'protected employment': The 'positive transitioning effect' of trade unions - Melisa R. Serrano; Edlira Xhafa (International Labour Organization (ILO), 2016)
This paper aims at contributing to the discussions on the challenge of transitioning from precarious informal employment to more protected employment. This paper looks into a rather under-researched area - the role of trade unions in facilitating this process of 'transitioning' as well as in containing the spread of this type of employment. We refer to this process, along with its outcomes, as the 'positive transitioning effect' of trade unions. Through 10 case studies from nine countries (Brazil, India, Israel, Nepal, Nigeria, the Philippines, South Korea, the UK, and Zambia), the paper analyses several factors, such as the legal framework (i.e., labour laws and regulations), economic and social protection measures beyond the labour law, union's organisation structures and processes, and union strategies and measures, that influence the success of various 'transitioning' initiatives undertaken either solely by trade unions or in collaboration with other organisations. In facilitating the transition to more protected employment, trade unions have used these factors to draw on and develop various power resources: institutional, associational, structural and social power. The paper shows that, among the various dimensions of these power resources, institutional vitality plays a critical role in reinforcing the unions' ability to make strategic choices not only to resist the informalisation of work but also to initiate and push for positive changes in the world of work.
Keywords: 330; precarious employment; informal workers; employment security; trade union role; case study; Brazil; India; Israel; Korea R; Nepal; Nigeria; Philippines; UK; Zambia